Mechanical and Thermal Properties of Graphene based Hybrid Polymer Nanocomposites - A Review. Issue 1 (April 2021) - Haider, Mohd. Rehan; Kumar Singh, Pradeep
Abstract: Graphene-based materials are platelets of one or several layers that can be supplied by substance techniques in mass quantities. Therefore we present a report on polymer nanocomposites, including late work using graphite nanoplatelet fillers, using graphite-based fillers. In addition to techniques for the dispersion of these materials in various polymer grids, various courses used to manufacture graphemic materials are discussed. In addition, the mechanical and thermal characteristics of these composites are examined and The characteristics of graphene-based materials and their dispersion condition in the grid will be studied. A diagram of possible uses for these composites and existing challenges in the field is geared to the future and is aimed at enhancing the materials that are promising. In this review, the analysis of a few decent articles focused on half and half of the composites of graphene and The adaptive impact of graphene with the other nanoparticles in order to calculate its effects on the composite mechanical properties.